2008
DOI: 10.1002/bmb.20235
|View full text |Cite
|
Sign up to set email alerts
|

Glucose as the sole metabolic fuel: The possible influence of formal teaching on the establishment of a misconception about energy‐yielding metabolism among students from Rio de Janeiro, Brazil

Abstract: Energy-yielding metabolism is an important biochemistry subject that is related to many daily experiences and health issues of students. An adequate knowledge of the general features of EYM is therefore important, both from an academic and social point of view. In a previous study, we have shown that high-school students present the misconception that carbohydrates, especially glucose, are the sole metabolic fuel for ATP production by human cells. In the present work, we investigated the possible origins of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
1
10
0
5
Order By: Relevance
“…The difference between the two situations was significant ( X 2 = 8.687, p = 0.0338) . Those results are fully compatible with previous reports showing that the misconception is established in grade school and later reinforced at the first year of high school [].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The difference between the two situations was significant ( X 2 = 8.687, p = 0.0338) . Those results are fully compatible with previous reports showing that the misconception is established in grade school and later reinforced at the first year of high school [].…”
Section: Resultssupporting
confidence: 93%
“…Students' misconceptions regarding EYM were characterized on three different occasions. First, students answered the same questionnaire (Q1) used in previous studies [], which was meant to allow comparison of the results obtained with those reported in previous studies. The Q1 was answered anonymously by the students two days before the teaching of the EYM teaching unit (EYM‐TU) and consisted of two objective questions: 1) “What happens to the overall ATP production in an individual fed on a low carbohydrate diet?” and 2) “What happens to the overall ATP production in an individual undergoing prolonged (many days of) fasting?” Students had the same four choices to answer to each question: “I do not know”; “ATP production remains unchanged”; “ATP production increases”; or “ATP production decreases.” Three lines were available after the choices for the students to briefly justify their answers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies demonstrated misconceptions prevailing throughout courses [69]. Current methods to test conceptual understanding and uncover misconceptions include: multiple choice questions (MCQs) with or without written explanations [4, 6, 1017]; MCQs including a confidence test [18]; open questions [19]; generating MCQ questions by the student [20]; drawing [21] or selecting drawings [22]; individual interviews [21, 23]; laboratory instructions with or without (verbal) predictions of the outcome of the experiment [24]; online self-directed E-learning modules [25]; or in-depth interviews with teachers to explore their perceptions of student’s misconceptions [3]. …”
Section: Introductionmentioning
confidence: 99%